THE EFFECT OF SMALL GROUP DISCUSSION METHOD ON THE ABILITY OF THE SECOND YEAR STUDENTS OF SMK MUHAMMADIYAH 2 PEKANBARU IN COMPREHENDING REPORT TEXTS - Widia Anggraini; Syofia Delfi; Masyhur Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research was aimed to find out the ability of the second year students of SMK Muhammadiyah 2 Pekanbaru in comprehending report texts. The data were collected from April to May. The population of this research is the second year students of SMK Muhammadiyah 2 Pekanbaru. The number of sample is 39 students who are chosen by using cluster sampling technique. This research is a pre experimental research with one group pre-test post-test design. The result of the data analysis showed that the mean score of pre-test is 61.33 while in post-test is 78.13. It showed us that the mean score of the post-test was higher than the mean score of the pre-test. In other words, Alternative Hypothesis (Ha) is accepted and Null hypothesis (Ho) is rejected. It means that, there is a significant effect of Small Group Discussion method on the ability of the second year students of SMK Muhammadiyah 2 Pekanbaru in comprehending report texts. It is suggested that Small Group Discussion is one of the appropriate method to be implemented in teaching for comprehending report texts. It can be conducted by focusing to the students’ context.Keywords: Comprehension, Small Group Discussion Method, Report Texts.